Building a heaven on earth : religion, activism, and protest in Japanese occupied Korea - Park, Albert L. (University of Hawaiʻi Press, 2015)
This work examines the progressive drives by religious groups to contest standard conceptions of modernity and forge a heavenly kingdom on the Korean peninsula to relieve people from fierce ruptures in their everyday lives. The results of this study will reconfigure the debates on colonial modernity, the origins of faith-based socialactivism in Korea, and the role of religion in a modern world.